2020
DOI: 10.1186/s12864-020-6477-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of laser-captured germ cells and functional characterization of zbtb40 during 17alpha-methyltestosterone-induced spermatogenesis in orange-spotted grouper (Epinephelus coioides)

Abstract: Background: Spermatogenesis is an intricate process regulated by a finely organized network. The orange-spotted grouper (Epinephelus coioides) is a protogynous hermaphroditic fish, but the regulatory mechanism of its spermatogenesis is not well-understood. In the present study, transcriptome sequencing of the male germ cells isolated from orange-spotted grouper was performed to explore the molecular mechanism underlying spermatogenesis. Results: In this study, the orange-spotted grouper was induced to change s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
(52 reference statements)
2
13
0
Order By: Relevance
“…Prior to our current study, there was no reports about the sexual dimorphism of rergl that implied its potential role in sex regulation. However, unlike other genes, cyp17a1 exhibited an entirely different expression pattern in ovary and testis and its distribution varied in different germ cells [41]. The condition of cyp17a1 hinted at the distinct roles in female and male which is agreed with the results in zebrafish [42].…”
Section: Discussionsupporting
confidence: 82%
“…Prior to our current study, there was no reports about the sexual dimorphism of rergl that implied its potential role in sex regulation. However, unlike other genes, cyp17a1 exhibited an entirely different expression pattern in ovary and testis and its distribution varied in different germ cells [41]. The condition of cyp17a1 hinted at the distinct roles in female and male which is agreed with the results in zebrafish [42].…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we concluded that the zf-C2H2 protein was the most abundant type of TF in lenok, and its specific function should be further studied. The ZBTB family refers to a class of proteins containing the N-terminal BTB domain and multiple zinc finger domains at the C-terminal ( 48 ), and more than 60 types of ZBTB proteins have been identified as being involved in development, differentiation, and tumor formation ( 49 ). Recent studies have shown that zbtb16 can regulate spermatogenesis by controlling the self-renewal and repair of spermatogonia ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that zbtb16 can regulate spermatogenesis by controlling the self-renewal and repair of spermatogonia ( 50 , 51 ). In orange-spotted grouper, zbtb40 is specifically expressed in male germ cells and regulates spermatogenesis through its interaction with cyp17a1 ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germ cell marker genes can be used for exploring PGCs formation and migration, germ cell development, and the mechanism behind gametogenesis. In teleost fish, some germ cell-specific genes have been characterized, including PGC-specific gene Nanos3 [ 4 ], mitotic germ cell-specific gene Ly75 [ 5 ], spermatogonium-specific gene Plzf [ 6 , 7 ], oocyte-specific gene Slbp2 [ 8 ], as well as the well-known germline-specific genes Vasa , Dazl and Piwi [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%